Reef fish resilience following a significant earthquake disaster in the Nias Islands, Indonesia - RISANDI DWIRAMA PUTRA; RIKOH MANOGAR SIRINGORINGO; MUHAMMAD ABRAR; NI WAYAN PURANAMASARI; DIETRIECH GEOFFREY BENGEN; NEVIATY PUTRI ZAMANI; BEGINER SUBHAN; LUDI PARWADANI AJI; GIYANTO GIYANTO; INDRA PUTRA ALMANAR; EFRIN ANTONIA DOLLU (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Putra RD, Siringoringo RM, Abrar M, Puranamasari NW, Bengen DG, Zamani NP, Subhan B, Aji LP, Giyanto, Almanar IP, Dollu EA. 2025. Reef fish resilience following a significant earthquake disaster in the Nias Islands, Indonesia. Biodiversitas 26: 1836-1845. The geological upheaval of the Nias Islands, Indonesia, due to a major earthquake in 2005, resulted in lithospheric shifts, causing a sea floor uplift of approximately 1-2 meters. This uplift led to localized coral mortality, posing a threat to certain reefs and consequently impacting the composition of coral reef fishes. This study aims to explore the enduring changes in coral reef fish composition before and after the earthquake. Underwater Visual Census (UVC) transect surveys were conducted using standard SCUBA diving equipment to quantify fish abundance and biomass in benthic substrate transect locations. The reef fish assemblages categorized into corallivores (Chaetodontidae), herbivores (Acanthuridae, Scaridae, and Siganidae), and carnivores (Haemulidae, Lethrinidae, Lutjanidae, and Serranidae), were studied from eight fish families, with species identification conducted at the individual level. Analysis of corallivorous fish abundance during the pre-earthquake period (2004), earthquake event (2005), and post-earthquake recovery (2007-2010) revealed no significant differences (Kruskal-Wallis, p: 0.58). Corallivore abundance was lower in the pre-earthquake conditions, increased during the earthquake (Pairwise Wilcoxon test, p-value: 0.74), decreased in 2007 (Pairwise Wilcoxon test, p-value: 0.071) after the disturbance, but rebounded in 2008 (Pairwise Wilcoxon test, p-value: 0.23). Post the seismic event in 2005, ecological indices reflecting Shannon diversity (H’) and Uniformity Index Evenness (J) among reef fish, especially the corallivore group, consistently displayed a noticeable decline. However, recovery progress levels were exclusively regained by 2010.